Managing Disease Information: The Communication of Islamic Organizations During Covid-19 Outbreak in Indonesia - D.I. Ansusa Putra; Adeni Adeni (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
The presence of COVID-19 has changed the religious information of Islamic organizations in Indonesia. To a certain extent, religious organizations play an essential role in handling outbreaks regarding their strategic position as opinion leaders for society. This study seeks to examine the religious discourse changes of Nadhlatul Ulama (NU) and Muhammadiyah in responding to the pandemic as portrayed on their official websites. This study uses a qualitative method with a critical discourse analysis approach from van Dijk (2001), in which language is analyzed by describing the aspects of language (texts) and relating to the context and social cognition. The study concludes that the state/government's power relation dominates NU and Muhammadiyah's discourses. Nahdatul Ulama (NU) tends to show the theological-normative things based on culture, while Muhammadiyah discusses religious narratives based on charity and transformative actions. However, both of them are developing contextual fiqh and disaster fiqh facing the COVID-19 pandemic based on the Quran-Hadis direction.